2021
DOI: 10.3390/met11122039
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Inhibit Intergranular Corrosion in Ferritic Stainless Steel Welds Using High-Speed Laser Cladding

Abstract: Ferritic stainless steels are prone to localized corrosion phenomena such as pitting corrosion or intergranular corrosion, in particular when jointed by fusion welding processes. State-of-the-art techniques to avoid intergranular corrosion mainly consist of alternating alloy concepts or post-weld heat-treatments—all of which are associated with increased production costs. Hence, the present investigation seeks to introduce a novel approach for the inhibition of intergranular corrosion in ferritic stainless ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Moreover, the grooves evolving from IGC appear deeper and, thus, more significant. Overall, the temporally resolved mass loss is in good agreement to the evolution of residual mechanical strength of laser-cladded AISI 430 welds which features an approximate exponential decline [33]. In summary, the presented results indicate that the use of comparatively short pulse durations during P-LBW can inhibit chromium carbide precipitation, sensitization and, consequently, IGC within the HAZ due to the inherent thermal gradients and rapid cooling rates, which are obviously amplified in comparison to cw-LBW.…”
Section: Precipitation Kinetics and Intergranular Corrosion Behavioursupporting
confidence: 72%
See 2 more Smart Citations
“…Moreover, the grooves evolving from IGC appear deeper and, thus, more significant. Overall, the temporally resolved mass loss is in good agreement to the evolution of residual mechanical strength of laser-cladded AISI 430 welds which features an approximate exponential decline [33]. In summary, the presented results indicate that the use of comparatively short pulse durations during P-LBW can inhibit chromium carbide precipitation, sensitization and, consequently, IGC within the HAZ due to the inherent thermal gradients and rapid cooling rates, which are obviously amplified in comparison to cw-LBW.…”
Section: Precipitation Kinetics and Intergranular Corrosion Behavioursupporting
confidence: 72%
“…The use of EBSD-based phase mappings at a high magnification facilitates a robust and prompt means to characterize chromium carbide precipitates at the WM/HAZ boundary [33], whose dimensions following cw-LBW typically lie in the order of tenths to hundreds of nanometres [31]. The crystallographic investigation in Fig.…”
Section: Precipitation Kinetics and Intergranular Corrosion Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Sommer et al [31] investigated the intergranular corrosion of unstabilized AISI 430 FSS weldment produced by laser cladding at high speed. It is observed that the FSS weld joint was prone to intergranular corrosion due to the segregation of the alloy elements within the weld metal zone.…”
Section: Utilized Welding Methodsmentioning
confidence: 99%